The Impact of Nursing Services on Patient Satisfaction: A Scientific Analysis of Hospitals Under the Libyan Ministry of Health - Abdulrahman Anbeeh Fadhlulla Alwirfili; Ernawati; Yunie Armiyati; Ratih Sari Wardani; Fatkhkul Mubin (Babali Nursing Research, 2023)
Background: The success of nursing services depends on more than only the care and recovery of patients. The effectiveness of providing these services is governed not only by the knowledge and skills of medical workers. Objectives: This paper aims to evaluate the impact of nursing services on patient satisfaction: a scientific analysis of hospitals under the Libyan ministry of health. Methods: This study uses a descriptive analysis method to evaluate the effectiveness of nursing services conducted by the Libyan Ministry of Health. Data and information related to nursing services in hospitals managed by the Libyan Ministry of Health are collected and analysed to provide a clear picture of quality and safety of services, use of resources, and patient satisfaction. The PSNCQQ used to measuring the amount of predicted need, with 5-point Likert scale. Results: Patients with greater incomes and more education tend to be more satisfied with nursing treatment, income level and education level both have statistically significant impacts. Conclusions: This study concludes that the examination of the effectiveness of nursing services by the Libyan Ministry of Health provides significant benefits in improving service quality and patient satisfaction. Although there are some aspects that need to be continuously improved, the descriptive analysis method proves the effectiveness of this check as an important tool in improving the health system and providing better services to the people of Libya.